Strategi Komunikasi pada Marketing Communication PT. Global Sigma Mandiri dalam Mepengaruhi Pelanggan Melalui Media Sosial Whatsapp - Suheni, Suheni; Hardian, Arvin; Hadi, Sari Ekowati (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This research aims to analyze the communication strategy implemented by PT Global Sigma Mandiri in influencing customers through WhatsApp social media in the context of marketing communication. The method used in this research is a qualitative approach with descriptive analysis. Data were obtained through interviews with the company's marketing staff and analysis of WhatsApp content used in communication with customers. The results showed that PT Global Sigma Mandiri uses various approaches in marketing communication, including the delivery of customized promotional messages, personalized customer relationship management, and utilization of WhatsApp features to build two-way communication. Thus, WhatsApp as a communication platform is effective in increasing customer engagement and satisfaction.